Metformin treatment inhibits motility and invasion of glioblastoma cancer cells - Al Hassan, Marwa (2018)
Glioblastoma multiforme (GBM) is one of the most common and deadliest cancers of the central nervous system (CNS). GBMs high ability to infiltrate healthy brain tissues makes it difficult to remove surgically and account for its fatal outcomes. To improve the chances of survival, it is critical to screen for GBM-targeted anticancer agents with anti-invasive and antimigratory potential. Metformin, a commonly used drug for the treatment of diabetes, has recently emerged as a promising anticancer molecule. This prompted us, to investigate the anticancer potential of metformin against GBMs, specifically its effects on cell motility and invasion. The results show a significant decrease in the survival of SF268 cancer cells in response to treatment with metformin. Furthermore, metformin’s efficiency in inhibiting 2D cell motility and cell invasion in addition to increasing cellular adhesion was also demonstrated in SF268 and U87 cells. Finally, AKT inactivation by downregulation of the phosphorylation level upon metformin treatment was also evidenced. In conclusion, this study provides insights into the anti-invasive antimetastatic potential of metformin as well as its underlying mechanism of action.